Synthesis of Best Practices in Forensic Trace Evidence Analysis: Towards a Uniform Approach to Complexity Evaluation - T. M. Volkova (Теория и практика судебной экспертизы)
The paper addresses the problem of improving the practice of forensic trace evidence examinations with the help of criteria that affect the evaluation of their complexity. It offers a synthesis of data submitted by seven regional centers and four laboratories of the system of forensic science organizations of the Russian Ministry of Justice. It demonstrates that relevant parameters are not always taken into account when assessing the category of analysis complexity, which leads to underestimation of complexity measures in some cases. Recommendations are offered for the optimization of forensic practice to incorporate characteristics reflecting realistic conditions of actual forensic casework.